Effects of synthetic sheared flow on a utility-scale rotor in an open channel (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Computational studies have been conducted to demonstrate the effects of the proximity of tidal stream turbines to the mean sea level (MSL) or seabed (both encompassed in the device’s ‘local blockage’), subject to a uniform inflow [1]. Where, in reality, non-uniform flows interact with the turbine, influencing the performance, loading and wake dynamics.This study was conducted to investigate the influence of a sheared inflow condition on the performance of a utility-scale turbine. This was employed numerically to give insights into a utility turbine's arising power, thrust and wake recovery.For turbulence closure, a Wall-Adapting Local Eddy-viscosity [2] Large Eddy Simulation (LES) approach was used, alongside an in-house embedded actuator line model [3-4] to simulate the rotor and generate its induced unsteady wake dynamics. The Divergence-Free Synthetic Eddy Method (DF-SEM) [5] was used to generate the non-uniform inflow turbulence. This method principally relies on the specification of the velocity profile and Reynolds Stress tensor distribution at the inlet; both were obtained using scaled DNS data for fully developed open-channel flow [6], assuming Reynolds number independence.The study was conducted for a 22-metre diameter turbine (scaled from a lab-tested benchmarking tidal turbine [7]) in a 36-metre depth, 500-metre width channel, matching the channel blockage of the previous study encompassing the uniform inflow case (2.1%) [1]. A sensitivity study was conducted to assess the dominant effects on the device performance and arising wake dynamics.  Towards the seabed, the DF-SEM inflow showed reduced thrust and power due to the lower velocities than the uniform inflow. The rotor mass flux difference suggests the need for alternative normalisation to compare performance coefficients. Nonetheless, reduced performance shows power overestimation with the bottom-fixed uniform-inflow caseHigher near-seabed turbulence, flow non-uniformities and favourable flow gradients between core and bypass flows aided wake recovery by improving high-energy flow entrainment, the onset of wake destabilisation, and turbulent mixing. Further analysis will be conducted to quantify the rotor performance and dominant energy extraction mechanisms.References• X. Chen, B. Msutwana and R.H.J Willden, Anisotropic local effects and turbine interference on a utility-scale multi-rotor tidal energy system, Innovations in Renewable Energies Offshore, 1, 73-80, 2024.• F. Nicoud and F. Ducros, Subgrid-scale stress modelling based on the square of the velocity gradient tensor, Flow, Turbulence and Combustion, 62(3), 183-200, 1999.• J. Schluntz and R.H.J. Willden, An actuator line method with novel blade flow field coupling based on potential flow equivalence, Wind Energy, 18(8), 1469-1485, 2015.• A. Wimshurst and R.H.J. Willden, Validation of an actuator line method for tidal turbine rotors, Ocean Engineering, 163, 251-263, 2018.• R. Poletto, T. Craft, and A. Revell, A new DF-SEM for the reproduction of inlet flow conditions for LES, Flow, Turbulence and Combustion, 91(3), 519-539, 2013• J. Yao, X. Chen, and F. Hussain, Direct numerical simulation of turbulent open channel flows at moderately high Reynolds numbers, Journal of Fluid Mechanics, 953, A19, 2022• Tucker Harvey et al., Tidal Turbine Benchmarking Project: Stage I – Steady Flow Experiments, Proceedings of the 15th EWTEC, 3-7 Sep, 2023, Bilbao.